Increased Susceptibility to Atrial Fibrillation Secondary to Atrial Fibrosis in Transgenic Goats Expressing Transforming Growth Factor‐β1. (30th August 2016) - POLEJAEVA, IRINA A.; RANJAN, RAVI; DAVIES, CHRISTOPHER J.; REGOUSKI, MISHA; HALL, JUSTIN; OLSEN, AARON L.; MENG, QINGGANG; RUTIGLIANO, HELOISA M.; DOSDALL, DEREK J.; ANGEL, NATHAN A.; SACHSE, FRANK B.; SEIDEL, THOMAS; et al.
AF Susceptibility in TGF‐β1 Transgenic Goats: Introduction: Large animal models of progressive atrial fibrosis would provide an attractive platform to study relationship between structural and electrical remodeling in atrial fibrillation (AF). Here we established a new transgenic goat model of AF with cardiac specific overexpression of TGF‐β1 and investigated the changes in the cardiac structure and function leading to AF. Methods and Results: Transgenic goats with cardiac specific overexpression of constitutively active TGF‐β1 were generated by somatic cell nuclear transfer. We examined myocardial tissue, ECGs, echocardiographic data, and AF susceptibility in transgenic and wild‐type control goats. Transgenic goats exhibited significant increase in fibrosis and myocyte diameters in the atria compared to controls, but not in the ventricles. P‐wave duration was significantly greater in transgenic animals starting at 12 months of age, but no significant chamber enlargement was detected, suggesting conduction slowing in the atria. Furthermore, this transgenic goat model exhibited a significant increase in AF vulnerability. Six of 8 transgenic goats (75%) were susceptible to AF induction and exhibited sustained AF (>2 minutes), whereas none of 6 controls displayed sustained AF (P < 0.01). Length of induced AF episodes was also significantly greater in the transgenic group compared to controls (687 ± 212.02 seconds vs. 2.50 ± 0.88 seconds, P < 0.0001), but no persistent or permanent AF was observed. Conclusion: A novel transgenic goat model with a substrate for AF was generated. In this model, cardiac overexpression of TGF‐β1 led to an increase in fibrosis and myocyte size in the atria, and to progressive P‐wave prolongation. We suggest that these factors underlie increased AF susceptibility.